2015
DOI: 10.1371/journal.pmed.1001811
|View full text |Cite|
|
Sign up to set email alerts
|

Improving Men’s Participation in Preventing Mother-to-Child Transmission of HIV as a Maternal, Neonatal, and Child Health Priority in South Africa

Abstract: Wessel van den Berg and colleagues outline how increasing male partner involvement in efforts to reduce mother-to-child HIV transmission in South Africa may improve maternal and infant outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 34 publications
1
35
0
Order By: Relevance
“…The findings of this study supported the study conducted in South Africa which revealed that the male partners who had high monthly income were more involved in PMTCT of HIV services than respondents who had low monthly income [1]. This low involvement might be due to lack of awareness about PMTCT service which are given free of fee in all governmental health facilities and sociodemographic characteristics of the respondents.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The findings of this study supported the study conducted in South Africa which revealed that the male partners who had high monthly income were more involved in PMTCT of HIV services than respondents who had low monthly income [1]. This low involvement might be due to lack of awareness about PMTCT service which are given free of fee in all governmental health facilities and sociodemographic characteristics of the respondents.…”
Section: Discussionsupporting
confidence: 84%
“…Mother-to-child transmission is the most common mode of human immunodeficiency virus (HIV) transmission in children which can be vertically transmitted from HIV positive pregnant women to their unborn babies during pregnancy, labour, and delivery or through breastfeeding after delivery [13]. HIV remains a major challenge globally regardless of decades of advocacy and investment in programs to control the spread of the virus [4, 5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We propose that safer conception activities be incorporated into evolving UTT implementation plans and targets since this would represent an efficient alternative to a lengthy parallel process of developing a standalone safer conception framework. Integration of safer conception activities into the UTT plans finds congruence with 90:90:90 goals given the potential impact safer conception services may have on HCT and ART uptake, adherence and client retention, and viral suppression, particularly amongst men [15,30,31]. …”
Section: Discussionmentioning
confidence: 99%
“…Engaging men may also lead to gender-based violence, if couples are serodiscordant (34, 35). Given a lack of standardization of interventions and varying rigor in evaluation of impact, it is not surprising that both success and failure are reported, with uncertainties as to best practices and whether the added costs of male partner engagement have an evidence-based justification (8, 25, 36, 37). …”
Section: Introductionmentioning
confidence: 99%